Lietuvos valdovo titulas ir valdžia XIV a. pab. - XV a. viduryje - Skurvydaitė, Loreta (Lietuvos istorijos studijos, 1999)
Title of the Lithuanian ruler was developed during the most difficult period of Lithuania's history which coincide with the consolidation of personal and national power of Vytautas in the Polish-Lithuanian union. While establishing the self-independent Lithuanian state, Vytautas create the title of Lithuanian ruler Magnus Dux Lithuaniae, Russiae etc. According to the agreements between Jogaila, the king of Poland and Vytautas, the latter acquired the title of the duke of 'Irakai first, followed by duke of Lithuania and finally the Grand Duke. In foreign affairs, Vytautas acted using the highest title, which he styled himself, while trying to reach this status in the GDL in a legal way. This large variety of Vytautas' titles can be explained by the lack of settled norms concerning the titles. Nevertheless, the political conception of Vytautas - the establishment of an independent Lithuanian state ruled by independent rulers - found its representation in the field of sphragistics and titles. The title of grand duke was a part of Vytautas' political programme which had to be fulfilled by the crown of a king.When the conflict for the Vytautas heritage started, the position of the Lithuanian ruler towards the sovereign rule as well as the title became very complicated. The title of the grand duke of Lithuania did not coincide automatically with the content of the power of the Lithuanian ruler. It was impossible to become the ruler of Lithuania without the acknowledgment of the grand duke title. Vytautas created this grand duke title using his real power in the country, i.e. being the actual ruler. His successors Švitrigaila and Žygimantas Kęstutaitis, while having this, already created, title tried to consolidate their power. Vytautas established this title while using his power; Žygimantas Kęstutaitis used his title to consolidate his rule over the country. The title of the grand duke became the reality of Lithuanian political life and the rulers used it for their policy.